Research of Variable Speed Characteristic of Transmission Mechanism of Rod-Gear Type Pulsation CVT - Chen Suifan; Dong Zhifeng (Jixie chuandong)
Based on the analysis of transmission mechanism of rod-gear type Pulse Continuously Variable Transmission（ P-CVT）,the closed vector equations of equivalent plane six-bar mechanism is built,and the kinematic mathematical model of angular displacement,angular velocity and angular acceleration of connecting rod,rocker and meshing point to input shaft axis of single phase transmission mechanism is constructed by the matrix method. At last,by using software Matlab,the simulation analysis of the effects of speed-adjusted style,phase number and eccentricity on the speed-variation characteristics,the main speed regulating mode and the optimal phase number are the determined,the advantages of large variable speed ratio range and small pulsation rate the transmission mechanism are proved. The reference for improving the design theory and engineering implementation of the transmission is provided.